Desenvolvimento de formulação cosmética creme facial contendo o pó da folha de noni obtido através de secagem em camada de espuma - Silva, Ynis Thaciane Felix da (2024)
Foam layer drying is a thermal treatment used for the processing and consequent increase in the shelf life of perishable products due to the removal of water available for microbial activity. Noni (Morinda citrifolia L.) has several therapeutic purposes due to the existence of more than 200 phytochemical substances with bioactive properties that can be explored in the cosmetic and pharmaceutical areas. However, plant species deteriorate within a short period of time after being harvested due to the availability of water, meaning they need to be consumed or processed quickly, sold dry and packaged. Medications and cosmetic emulsions are commonly developed from plant compounds with diverse benefits. Emulsions, for example, are formulations used in skin care products in which two phases, one aqueous and the other oily, are combined in order to obtain a pleasant product with the capacity to provide benefits to the skin and often have as the main constituent, plant active ingredients. This work aimed to develop a facial cream from noni leaf powder obtained through drying in a layer of foam. Parameters of the powder obtained and the cosmetic formulation developed were analyzed. Starting with the analysis of the powder, the adsorption isotherms were determined in order to understand the perishability of the product for storage. Mathematical adjustments were made to the isotherms obtained with three different mathematical models. The Oswin model was the one that best represented empirical adjustments describing the process. Thermogravimetric analysis was carried out in order to investigate the thermal stability of the noni leaf powder and the cosmetic formulation in the temperature range of 30 to 600 ºC and in an inert nitrogen atmosphere under heating rates of 10, 20 and 40 ºC/ min. Isoconversional mathematical models were used to adjust the degradation kinetics, which proved to be effective in terms of degradation mechanisms, which was observed from the R2 values obtained. Noni leaf powders obtained by drying in a foam layer showed high hygroscopicity under all conditions of production, presenting water activity (Aw) that varied from 0.098 to 0.969; the isotherms were classified as Type III (sigmoidal). The thermal behavior of noni leaf powder in an inert atmosphere is the same when compared at the same heating rates, which indicates that the conditions for obtaining the powder do not influence its decomposition process. With thermal analysis, it was possible to observe a gradual loss of mass for the noni leaf powder in all samples studied, which indicates that the samples are thermally unstable since the Activation Energy (Ea) determined did not show significant differences between the samples, indicating that the experimental conditions used to obtain the powder did not influence the degradation process. With the present study, it was therefore possible to conclude that noni leaves enable the development of formulations that meet the organoleptic and sensory requirements of a cosmetic preparation.